(untitled) (Research, Society and Development, 2019)
This work aims to share some reflections about the contemporary school in the interface of an experience in the classroom. In this context, the theoretical framework is based on a pedagogical experience focusing on Financial Mathematics, applied to the third year of high school in a State School of Vale do Taquari/RS, in the first quarter of 2015. The purpose of this proposal was to link the content programmed through the School Study Plan, with a subject related to the daily life of the students. Through provided activities, it was possible to offer several reflections, since it was noticeable the discouragement and lack of motivation of the students in the classroom. For that, authors dealing with this theme were used, such as Ó and Costa, Nóvoa, Ghedin and Pérez Goméz. It should be emphasized that it is necessary to rethink the role of the school and the challenges to be overcome, so that it becomes ever more attractive and provides the student with a more involving environment. It is emphasized that motivation originates in the desire to satisfy a need, if there is no need, there will be no motivation. Therefore, it is highlighted that through the pedagogical proposal, it was possible to point out ways to overcome some difficulties encountered by the students, promoting, in a motivating way, interactions between the content in study and the daily life of the student.